Shrinkage deformation of different shape of foamed concrete specimen - Zuhairi, Zakaria (2010)
In construction field, the most important element is concrete. Majority of construction in Malaysia use the concrete and the improvement of concrete technology is very important. Example of concrete technology improvement is foamed concrete. Foamed concrete is additional of foaming agent in the concrete mixture to control the concrete density and the foamed concrete do not used the course aggregate. The foaming agent used to trap the air to reduce the concrete density. The strength of foamed concrete is lower than normal concrete and it is suitable to be used at the uncritical structure in the construction. The foamed agent also expose to crack effected by drying shrinkage. Some of the factors causes the drying shrinkage are investigated. Two factors of drying shrinkage investigated in this study are different density of foamed concrete and different shapes of concrete specimens. Prism sized 100mm x 100mm x 500mm, cylinder sized 150mm 0 x 300mm and 150mm cube for 1200 kg/m3 and 1600 kg/m3 density were produced throughout this experiment. The uses of prism and cylinder specimens are because it is normal shape of concrete structure with different surface expose to environmental for shrinkage observation. The cube was used for compressive strength test to prove the targeted density. The result of compressive strength test shows the increments of concrete density produced high strength of concrete. On the other hand, the increments of concrete density reduce the shrinkage value as well as the reduction of surface exposes to the environmental.